Morphological variations and adhesive distribution: a cross-species examination in Colletotrichum conidia - Caleb Oliver Bedsole; Mary Cowser; Timothy Martin; Jillian Hamilton; Lucia Gonzalez Rodriguez; Thomas M. Chappell; Brian D. Shaw (Frontiers in Fungal Biology)
Colletotrichum is a globally significant genus of plant pathogens known for causing anthracnose across a diverse array of hosts. Notably, Colletotrichum graminicola is a pathogen affecting maize. Annually, the global economic impact of this pathogen reaches billions of US dollars. C. graminicola produces conidia that have a characteristic falcate shape and are dispersed by rain. Upon attachment to maize leaves, these conidia develop melanized appressoria to penetrate the leaf surface to initiate disease. Recent findings have emphasized the existence of an adhesive strip on only one side of C. graminicola conidia. This strip colocalizes with an actin array, playing a crucial role in facilitating attachment and germination. This asymmetrical adhesive was postulated to enhance spore dispersal by assuring that some conidia do not attach to their initial deposition site. The extent of this asymmetric adhesive phenotype in other Colletotrichum species remains unknown, raising questions about its conservation within the genus. This study reveals the ubiquitous presence of an asymmetric adhesive on the conidia across nine isolates of Colletotrichum, representing eight species. Morphological differences in conidium shape and adhesive distribution were observed. Significantly, Colletotrichum truncatum is unique from other observed species by exhibiting an adhesive strip on both sides of its conidium. Furthermore, in C. graminicola, we noted a simultaneous development of the actin array and detachment from its mother cell after spore development. We posit that the study of other Colletotrichum members holds promise in elucidating the evolutionary trajectory of this phenotype. Furthermore, these insights may prove instrumental in understanding spore dispersal dynamics across diverse hosts, shedding light on the intricate web of host specificity within the genus.